Effect of steviosides and potassium sorbate on the growth and thermal inactivation of Zygosaccharomyces bailii in acidified model aqueous systems - Schelegueda, Laura Inés (2017)
Zygosaccharomyces bailii growth and thermal inactivation curves were obtained in acidified aqueous systems, simulating low sugar products. Growth curves were fitted with Gompertz equation, while thermal inactivation curves were modeled using Baranyi equation. The parameters of the models were estimated and the effect of steviosides (EE) and potassium sorbate (KS) on the growth and survival of Z. bailii was established. The addition of KS decreased Z. bailii growth rate and increased its inactivation rate. The presence of EE promoted Z. bailii growth and protected yeast from thermal treatment. The joint use of KS and EE decreased the growth and nullified the protective effect of the sweetener on thermal inactivation. Results allow the selection of the appropriate concentrations of EE and KS to ensure the microbiological stability of evaluated systems and contribute to the development of low sugar products.